Identifying associated risk factors for severity of diabetic retinopathy from ordinal logistic regression models. Issue 1 (1st January 2018) - Kulothungan, Vaitheeswaran; Subbiah, M.; Ramakrishnan, R.; Raman, Rajiv
ABSTRACT: The realm of medical statistics or epidemiology encourages the repeated application of few variants of generalized linear model. This work has identified a situation in understanding the risk factor modelling for diabetic retinopathy, major source for blindness in adults and associated with Type II diabetes. Main objective of this study is to retain the ordinal nature of the response variable, one of the main concerns in ordinal regression procedures; and to emphasize the need for applying stereotype regression for bio medical data. Analysis plan envisaged in this study has shown the relevance and scope to extend the use of ordinal regression models.